Electric field and frequency dependent scaling behavior of dynamic hysteresis in the epitaxial (Pb0.9La0.1)(Zi0.4Ti0.6)O3 films. Issue 1 (18th November 2021) - Meng, Xudong; Song, Jianmin; Liu, Tianyi; Ma, Hongshuai; Liu, Baoting; Wang, Yinglong
Abstract: Epitaxial (Pb0.9 La0.1 )(Zi0.4 Ti0.6 )O3 (PLZT) film was prepared with Pt as the upper electrode and La0.5 Sr0.5 CoO3 (LSCO) as the bottom electrode on (001) STO substrate by radio frequency (RF) magnetron sputtering. The dynamic hysteresis scaling behavior of the film, including the variation of remanent polarization ( P r ), coercive field ( E c ), and loop area () with external field ( E 0 ) and frequency ( f), was systematically studied. The evolution of scaling behavior in the PLZT film can be divided into two stages: minor loops and major loops, which are in the low and high E 0 regions, respectively. The scaling relations take form of < A > ∝   f − 0.11   E 0 2.72 and < A > ∝   f − 0.03   E 0 1.27 in minor loops and major loops, respectively. The results show that the domain structure and domain reversal play an important role in the dynamic hysteresis behavior of ferroelectric materials.